Double Entry Book Keeping dan Accrual Basis Sebagai Pendukung Akuntabilitas Sektor Publik - Suryo Pratolo (Universitas Muhammadiyah Yogyakarta, Indonesia, 2001)
At the reformation era, the claim of transparency in all of area is the important thing. This claim happens mostly in governmental sector as core public organization that must give services for public needs. Basically, government is public believe holder, because of that it must be “amanah” by creating transparency and accountability at work in fulfill public needs. One of the ways to achieve transparency and accountability is doing public reporting well. It means that government must give high quality accounting information to public (parliament and other stakeholder). We all know that high quality accounting information will be achieved if it is relevant, reliable, auditable and traceable. In realizing this high quality of accounting information system we need so many factors. In this article we try to expose the double entry book keeping and accrual basis system in supporting the high quality of accounting information system that ultimately creating good clean governance in Indonesia.